A cidade estilhaçada : reestruturação econômica e emancipações municipais na baixada fluminense - Simões, Manoel Ricardo (2010)
This thesis has as objective to analyze the processes of municipal emancipation of the old districts of the city of Nova Iguaçu, in the Baixada Fluminense, Region Metropolitan of Rio De Janeiro, occurred in century XX. The conducting wire of this inquiry is the joint enters the process of economic development of the region and the successive occurred reorganizations of the organization social-spatial in this city that had implied in the sprouting of new social classrooms and groups politicians located in the districts. The appearance of great social-spatial inequalities provoked by the model of occupation of the ground and by the selective application of the investments of the city hall in public goods and services, provoked the questioning regarding the structures of being able local and of the legal-administrative order that discharge in social movements and alliances politics of construction of new territorial identities that consolidate in the municipal emancipations of Duque de Caxias, São João João de Meriti, Nilópolis, Belford Roxo, Queimados, Japeri and Mesquita. These emancipations had allowed to the ascent to the power of groups local politicians and the economic establishment of new projects and arrangements in the cities and a new composition of forces in the game politician of the Baixada Fluminense and in the State of Rio De Janeiro as a whole.